Whole genome sequencing in paediatric channelopathy and cardiomyopathy - Kwok, Sit Yee; Kwong, Anna Ka Yee; Shi, Julia Zhuo; Shih, Connie Fong Ying; Lee, Mianne; Mak, Christopher C. Y.; Chui, Martin; Tsao, Sabrina; Chung, Brian Hon Yin (Frontiers in Cardiovascular Medicine, 2024)
Precision medicine in paediatric cardiac channelopathy and cardiomyopathy has a rapid advancement over the past years. Compared to conventional gene panel and exome-based testing, whole genome sequencing (WGS) offers additional coverage at the promoter, intronic regions and the mitochondrial genome. However, the data on use of WGS to evaluate the genetic cause of these cardiovascular conditions in children and adolescents are limited.In a tertiary paediatric cardiology center, we recruited all patients diagnosed with cardiac channelopathy and cardiomyopathy between the ages of 0 and 18 years old, who had negative genetic findings with prior gene panel or exome-based testing. After genetic counselling, blood samples were collected from the subjects and both their parents for WGS analysis. A total of 31 patients (11 cardiac channelopathy and 20 cardiomyopathy) were recruited. Four intronic splice-site variants were identified in three cardiomyopathy patients, which were not identified in previous whole exome sequencing. These included a pathogenic variant in TAFAZZIN:c.284+5G>A (Barth syndrome), a variant of unknown significance (VUS) in MYBPC3:c.1224-80G>A and 2 compound heterozygous LP variants in LTZR1 (LTZR1:c.1943-256C>T and LZTR1:c1261-3C>G) in a patient with clinical features of RASopathy. There was an additional diagnostic yield of 1.94% using WGS for identification of intronic variants, on top of conventional gene testing. WGS plays a role in identifying additional intronic splice-site variants in paediatric patients with isolated cardiomyopathy. With the demonstrated low extra yield of WGS albeit its ability to provide potential clinically important information, WGS should be considered in selected paediatric cases of cardiac channelopathy and cardiomyopathy in a cost-effective manner.